An update on the copper corrosion program for the long‐term management of used nuclear fuel in Canada. Issue 1 (29th June 2020) - Keech, Peter G.; Behazin, Mehran; Binns, W. Jeffrey; Briggs, Scott
Abstract: In 2012, the Nuclear Waste Management Organization developed a comprehensive proof test plan (PTP) to evaluate the feasibility and safety of their copper‐coated used fuel container and their novel bentonite buffer box emplacement concept to be employed in its proposed deep geological repository for the long‐term management of used nuclear fuel. Research within the PTP includes several programs to evaluate the possible extent of damage that may be caused by various copper corrosion mechanisms: oxic‐, radiolytic‐, anoxic‐, and sulfide‐induced, with particular attention being paid to the possibility of localization of any of these processes. Programs remain on track to support and refine a maximum copper corrosion allowance of <1.27 mm over a one million year emplacement in a deep geological repository. Abstract : The Nuclear Waste Management Organization (NWMO) has been developing a technical and socially acceptable program for the long‐term management of Canada's used nuclear fuel. This paper summarizes the status and future direction of the NWMO corrosion program and provides insight into the total corrosion expected within the deep geological repository for Canada's copper‐coated used fuel containers.